Navigating Change and Safety with Mercury in an Installation by Rebecca Horn. Issue 2 (June 2023) - Hamilton, Emily; Sotek, Jeff; Poletski, Steve
The Hydra-Forest: Performing Oscar Wilde (1988) by Rebecca Horn was created with a significant volume of mercury as part of a multi-component installation. This work was acquired by the San Francisco Museum of Modern Art (SFMOMA) in 1990 and was examined prior to exhibition in 2017 to 2018. The mercury developed black accretions that were considered visually problematic. Concerns surrounding the health and safety of conservation treatment and exhibition were raised and the museum partnered with Amec Foster Wheeler (now WSP USA) to develop appropriate handling, treatment, and storage procedures. SFMOMA conservation and curatorial staff were in dialog with the artist's studio throughout this process and this collaborative process was essential in deciding how to exhibit this work moving forward.